2011
DOI: 10.5581/1516-8484.20120008
|View full text |Cite
|
Sign up to set email alerts
|

Confidential unit exclusion at the regional blood bank in Montes Claros

Abstract: ObjectiveThis study aimed at analyzing the rate of self-exclusion at the Regional Blood Bank in Montes Claros.MethodsData of self-excluding donors from August 2008 to August 2010 were analyzed. The following variables were considered: age, marital status, gender, ethnical background, blood group, Rh factor, number of donations, type of donation and serologic results.ResultsDuring the analyzed period, 34,778 individuals donated blood, 215 (0.62%) of which were self-excluded; 12% of donors did not answer, 6.3% b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…In our study, about one-third of the donors were first-time donors. Similar results were observed in several other studies in Iran and other countries [15,17,18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, about one-third of the donors were first-time donors. Similar results were observed in several other studies in Iran and other countries [15,17,18].…”
Section: Discussionsupporting
confidence: 92%
“…Donor selection is an important step in blood safety and different studies have revealed that suitable and appropriate donor selection can significantly improve blood safety [15,16]. It was shown that blood components of repeated and regular blood donors have a lower risk of TTI transmission than those of first-time donors [10,17,18,19,20]. On the other hand, it has been shown that first-time donors are the most common donors in blood transfusion centers [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous Brazilian studies on CUE use have shown rates of CUE use ranging from 0.62% to 3.3% while in our study 0.75% donors used CUE. CUE usage rates vary according to different socio‐educational and cultural factors.…”
Section: Discussionmentioning
confidence: 47%
“…( 4 ) During the last few years, several studies have been performed in an attempt to analyze the epidemiologic profile of self-excluding donors in Brazil as in the case of the article of the Regional Blood bank in Montes Claros, Minas Gerais State, Southeast Brazil published in this issue. ( 5 )…”
mentioning
confidence: 99%